Sistem Pakar dalam Mengidentifikasi Tingkat Keparahan Penyakit pada Tanaman Kelapa Sawit Menggunakan Framework Codeigniter - Yunita Cahaya Khairani; Gunadi Widi Nurcahyo (Jurnal Informasi dan Teknologi, 2021)
Palm oil is an industrial plant that produces oil (both cooking oil and fuel), soap and wax. One of the factors that can reduce the growth and productivity of oil palm is the presence of disease in the oil palm plant. In helping to identify and provide information about oil palm diseases, an Expert System was created to identify diseases in oil palm plants and their handling. The data that is processed in this research is knowledge about disease symptoms in oil palm plants which comes from an expert. The symptom data is processed using an expert system that has been designed and developed using the PHP Framework Codeigniter programming language and MySQL as the database. This system was successfully developed to identify the severity of the disease in oil palm plants and produce 100% accuracy. This system has been able to provide information to farmers about oil palm plant diseases and solutions to overcome them. This research is very suitable to be applied in identifying diseases in oil palm plants, so this research is suitable for use by oil palm farmers.